Denis Nosnitsin, ed., Ecclesiastic Landscape of North Ethiopia: Proceedings of the International Workshop Ecclesiastic Landscape of North Ethiopia: History, Change and Cultural Heritage. Hamburg, July 15–16, 2011 - Assefa, Daniel (Aethiopica, 2015)
Review